INFLUENCE OF FOOD INSECURITY ON ADHERENCE TO TREATMENT AND COMPLICATIONS OF TYPE 2 DIABETES MELLITUS IN BRAZIL: AN INTEGRATIVE REVIEW - Vinicius da Silva Pereira, Marcus; Saphira Araújo Costa, Alynne; Ferreira Sampaio, Ruan; Cácia Pereira Fernandes, Francisca; Castro Bezerra, Amélia; Vieira de Sousa Vilarinho, Adriana; Dilson Noleto Vilarinho Júnior, José; Wilker Santos Melo, José; Vitória Cruz Pavão, Katarina (Health and Society, 2023)
Type 2 diabetes mellitus is a chronic disease that affects millions of people worldwide, and food insecurity can aggravate the complications associated with this condition in patients living in situations of social vulnerability. We conducted an integrative literature review based on articles published in the Scielo, Google Scholar, and LILACS databases in the last five years. Ten articles were selected that addressed the most frequent complications in patients diagnosed with type 2 diabetes mellitus in situations of social vulnerability. The main complications found were diabetic neuropathy, diabetic nephropathy, diabetic retinopathy, and peripheral arterial disease. In addition, food insecurity was identified as a risk factor for the development and worsening of these complications in patients with type 2 diabetes mellitus.